Differences in knee flexor and extensor force and kinematic variables in rural versus urban area female students in Romania - Petre, Ioana Mădălina; Nobari, Hadi; Boscoianu, Mircea; Pelin, Bogdan; Ionescu, Anca; Prieto González, Pablo; Oliveira, Rafael; Oancea, Bogdan (Frontiers in Physiology, 2024)
The study aimed to identify and explain the typical differences in low-intensity high-volume resistance training (LIHV-RT) performances for major muscle groups between rural versus urban young female students to establish the relevant set of quantitative and qualitative resistance training parameters. The study sample included 46 recreational active female students at the Transilvania University of Brașov, (mean ± SD age, 20 ± 1 years; body mass, 60 ± 3 kg; height, 160 ± 4 cm) grouped urban vs. rural. The study used modified resistance exercise machines for the hamstring- and quadricep-group muscles, equipped with a dynamometer and sensors for identifying developed forces and accelerations. A number of 368 tests were performed, representing two attempts for each subject, for knee flexion and knee extension exercises, with two different loads. For the performance analysis some variables were considered: the maximum number of repetition until failure, maximum force developed, maximum acceleration, the duration of the set and the mean time per repetition. The maximum number of repetition to failure shows a significant higher value for rural than urban in case of knee flexion (d= 0.98 [0.32, 1.54] for load 1(L1) and d= 0.65 [0.03, 1.21] for load 2(L2)) and in case of knee extension (d=1.89 [1.11, 2.48] for L1 and d=1.67 [0.92, 2.25] for L2). The total duration of the sets shows a significant higher value for rural than urban in case of knee flexion (d= 0.84 [0.19, 1.39] for L2) and in case of knee extension (d=1.46 [0.74, 2.03] for L1 and d=1.56 [0.98, 2.14] for L2). Additionally we found differences in the quality of the relevant repetitions execution and in the impulse developed during the LIHV- MNRF sets. The study's main finding was that there are differences in LIHV-RT performances knee flexion and knee extension antagonistic exercises, between rural and urban female students. We concluded that the obtained results allow teachers to understand the optimal design of RT programs for the different groups of participants, in order to adapt their teaching techniques so that their final objectives are achieved, insisting on particular aspects of the theoretical or practical contents.